Anti-Robo: A Tool Detection System - Thutheja, V; Mohankar, V; Mulchandani, M (International Journal of Computer Sciences and Engineering, 2025)
Tool Detection System is a web application which detects those objects and tools that are not generally used in public places, which are more harmful to public like gun, knife, etc. When someone like robber, theft get inside the shop or ATM with having weapon like gun, knife and wear a mask, this tool detection system detects all unusual tools like guns that holed by robbers and send notification to the police station and we can easily stop happening robbery. This tool when capture image of tool or weapon and can subtract background image. After subtracting background image, the system checks the tool with the installed objects in the system and if matched then it sends notification and location to the nearby police station and related authority for the alert.